2007
DOI: 10.1007/s00421-007-0646-x
|View full text |Cite
|
Sign up to set email alerts
|

Sweat secretion from the torso during passively-induced and exercise-related hyperthermia

Abstract: Thermal sweating from the human torso accounts for about half of the whole-body sweat secretion, yet its intra-segmental distribution has not been thoroughly examined. Therefore, the aim of the current study was to provide a detailed description of the distribution of eccrine sweating within the torso during passively-induced (water-perfusion garment: 40 degrees C) and progressively increasing, exercise-related thermal strain (36 degrees C, 60% relative humidity). Sudomotor function was measured in ten males u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 15 publications
(37 reference statements)
10
50
0
Order By: Relevance
“…No significant differences in the T sk or changes in sweat ratio distribution between the anterior and posterior torso were observed between any of the conditions. This is consistent with current literature since higher RSR on the posterior compared to anterior torso have been observed both with (Havenith et al 2008a) and without the presence of wind (Machado-Moreira et al 2008b). Overall, regarding the influence of local T sk , it is concluded that when substantially changing it locally a clear effect is present (Nadel et al 1971a), but when looking at the natural variation over the body, as done here, this effect is of minor importance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No significant differences in the T sk or changes in sweat ratio distribution between the anterior and posterior torso were observed between any of the conditions. This is consistent with current literature since higher RSR on the posterior compared to anterior torso have been observed both with (Havenith et al 2008a) and without the presence of wind (Machado-Moreira et al 2008b). Overall, regarding the influence of local T sk , it is concluded that when substantially changing it locally a clear effect is present (Nadel et al 1971a), but when looking at the natural variation over the body, as done here, this effect is of minor importance.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the present data, Weiner (1945) found lower sweat rates on the posterior compared to anterior torso, however, the small sample size (n=3) may have been inadequate given the high variation in sweating between individuals. A medial to lateral decrease in sweat rate was observed across the torso in the present study and was similarly noted by Machado-Moreira et al (2008b) and Havenith et al (2008b), but not by Cotter et al (1995). Hertzman (1957) and Weiner (1945) similarly found lower sweat rates along the axillary line, supporting the present data.…”
Section: Discussionsupporting
confidence: 90%
“…The ventilated capsule (7.1 cm 2 ) was fixed to the upper section of the left scapula and the local sweat rate (LSR vc ) was measured during the exercise by using the ventilated capsule method [3][4][5][6][7][10][11][12][13]15,16] After the exercises, a part of the absorbent pad was pulled out from each of the tailored pads fixed on the skin. Each absorbent pad was quickly placed, separately, into an impermeable plastic Ziploc bag and weighed with the bag.…”
Section: Studymentioning
confidence: 99%
“…Previous studies of regional sweat rates found that the local sweat rate (LSR) clearly varies among the different body sites [1][2][3][4][5][6], and that LSR on the forehead and torso was greater than that of the limbs [1][2][3][4]. Some studies have focused on the differences in sweat regulation depending on maturation and aging [7][8][9][10][11], sex [12,13], fitness [8,14,15], and heat acclimation [8,16] to elucidate the mechanism underlying thermoregulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation